Impact of News Overload on Social Media News Curation: Mediating Role of News Avoidance - Zhang, Xiao; Akhter, Shamim; Nassani, Abdelmohsen A.; Haffar, Mohamed (Frontiers in Psychology, 2022)
In this global village, the easy access to news has brought about many changes in the preferences and patterns of people about accessing news. Therefore, the present study has attempted to investigate the effects of news relevance, perceived quality and news overloading on the news curation preferences of the people. This study has also examined the mediating role of news avoidance between the news relevance, perceived quality and news overloading on the news curation. A quantitative technique has been employed to check the relationships proposed in the study. A sample size of 217 has been analyzed to check these hypotheses. The findings of the study revealed that news relevance has a negative impact while news overload positively and significantly impact the news curation. However, the news avoidance only mediated the relationship of news quality and news curation. Theoretically, the study has contributed to the literature of journalism and social media by finding that relevance of news has a negative significant impact on the news curation behavior of people that if the news they do not find relevant they happily curate it. Practically, the study implies that the people are more prone to the quality of news rather than quantity; therefore, it is important for the news agencies to make sure that they produce and deliver the quality based news considering the accuracy to penetrate the theoretic last level.